Current Situation of the Efficiency of the National Budget Allocation in Vietnam - Trong Vinh, Nguyen; Nhung, Nguyen Cam (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 3, 2019)
This research evaluates the efficiency of the state budget allocation in Vietnam in the period 2007-2016 by using econometric models of OLS, FEM, REM and FGLS. The estimated results from the model, together with the evaluation of the state budget allocation show that the budget allocation has achieved positive results, but the efficiency of budget allocation is still not high. Following this, the article gives some policy implications for Vietnam to effectively allocate the state budget in the near future.